Developing an Emotional Wellness Counseling Program for Improving the Mental Health of Students in Islamic Boarding Schools - Jum Anidar; Nursyamsi Nursyamsi; Maiza Aznita; Suryadi Fajri; Aulia Rahmi Putri (Kuras Institute, 2026)
Mental health is an important aspect in the development of santri who live in a pesantren environment that is full of academic, social, and emotional pressures. This study aims to develop and test the effectiveness of the Emotional Wellness Counseling (EWC) based Counseling Guidance Program as an effort to improve the emotional well-being of students in West Sumatra pesantren. The method used is Research and Development (R&D) with the Mantap (Steady, Precise, Accurate, Productive) model which includes needs analysis, product development, expert validation, practicality test, effectiveness test, and dissemination. A total of 78 students from three pesantren were selected using simple random sampling technique. Data were collected through questionnaires, interviews, observations, and documentation, then analyzed using descriptive statistics f, feasibility validation, and pretest-posttest comparison. The results of expert validation showed that the EWC module was in the very feasible category (87-91%), while the practicality test by students and ustadz/ustadzah was in the very practical category (86-94%). The effectiveness test shows a significant increase in the ability of emotion regulation and emotional well-being of santri with an average N-Gain value of 0.64 (medium-high category) and an effect size of 0.81 which shows a large effect compared to the control class (N-Gain 0.32). The integration of Islamic values and Minangkabau cultural wisdom in the module strengthens the relevance and acceptance of the program in the pesantren environment. These findings confirm that EWC is effective and feasible to implement as an innovation in counseling services to strengthen the mental health of santri holistically.